Physicochemical characteristics of chemically treated bagasse fibers. Issue 1 (31st December 2022) - Prabhu, Roopa; Ganesh, Sharad; Mahesha, GT; Bhat, K Subrahmanya
Abstract: The present paper reports effect of chemical modification of bagasse fibers by using oxidizing agents like potassium permanganate and potassium dichromate. The fiber modification was assessed by several techniques like Fourier Transfer Infrared Spectroscopy (FTIR), Thermo Gravimetric Analysis (TGA), and X-Ray Diffraction (XRD) which provide evidences for the desired structural changes. Scanning electron microscope (SEM) used to analyze the microstructure of the samples. Our studies reveal decrease in the crystallinity index of samples after treatment with dichromate solution implying effective removal of polar impurities. Raw fibers had crystallinity index of 72% while permanganate and dichromate treated fibers showed 47% and 50%, respectively.